2019
DOI: 10.1002/jlb.3a0919-387rr
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of GITR/GITRL in attributes and immune responses of macrophage

Abstract: Glucocorticoid-induced tumor necrosis factor receptor family-related protein ligand (GITRL), a member of the tumor necrosis factor superfamily, is expressed in APCs and acts as a costimulatory molecule in the immune system. Although the glucocorticoid-induced tumor necrosis factor receptor-related protein (GITR)/GITRL system has been modulated to promote or decrease T cellrelated responses in multiple diseases, studies in macrophages are limited. To address this issue, we compared the expression of GITRL in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…This polarization of M2 toward M1-like macrophages is consistent with previous report in a pancreatic tumor model with low-dose radiation (30). We previously observed a peak of GITRL + macrophage on the first day after irradiation (data not shown), which is a marker of M1 macrophage (31). This peak typically resolved as Tregs were upregulated in the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…This polarization of M2 toward M1-like macrophages is consistent with previous report in a pancreatic tumor model with low-dose radiation (30). We previously observed a peak of GITRL + macrophage on the first day after irradiation (data not shown), which is a marker of M1 macrophage (31). This peak typically resolved as Tregs were upregulated in the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the fibrogenic factor TGF-β1 could induce hepatic progenitor cells to express GITRL, hepatic progenitor cells are another cell compartment expressing GITRL in chronic HBV-induced cirrhotic human liver tissue, and high GITRL expression correlates with disease severity and poor clinical outcome of HCC. Our overexpression and silencing data support the growth stimulatory effect of GITRL on hepatic progenitor cells, which is similar to the effect of GITRL on macrophages [ 38 ]. As a cell compartment involved in HCC carcinogenesis [ 8 , 9 ], hepatic progenitor cells expressing GITRL activate pathways of cancer, MAPK, PI3K/Akt and epithelial–mesenchymal transition by binding to ANXA2, which could enhance the progression of HCC [ 39 41 ] and many other tumours, including colorectal cancer [ 42 ], pancreatic cancer [ 43 ], breast cancer [ 44 , 45 ] and prostate cancer [ 46 ], suggesting that GITRL may contribute to the abnormal transformation of hepatic progenitor cells.…”
Section: Discussionsupporting
confidence: 83%
“…GITRL is an activating immune checkpoint ligand that binds to the GITR receptor. These immune modulators are key players in autoimmune diseases and in the immune responses of macrophages [ 51 , 52 ]. In our study, GITRL was significantly upregulated in OSCC tissue compared to NOM.…”
Section: Discussionmentioning
confidence: 99%